Electronic cigarette or vaping use among adolescents in the United States: A call for research and legislative action - Gilmore, Bretton; Reveles, Kelly; Frei, Christopher R. (Frontiers in Public Health, 2022)
Vaping among adolescents is increasingly common and may result in poor health outcomes; however, little research has been conducted evaluating the risks of vaping among adolescents and the knowledge and perceptions that drive use. We must gain a better understanding of vaping outcomes and adolescents’ perceptions while identifying potential ways to lessen or eradicate the health burdens associated with vaping. This knowledge could then inform robust educational and public health programs to prevent and mitigate vaping among youths. Health education incorporating a target populations’ world view, spheres of influence, readiness, motivation, intention, and determination promotes informed decision making. There are few resources currently being allocated to the problem even though legislators and enforcement agencies are aware. We cannot simply rely on existing laws to serve as a sufficient deterrent to prevent underaged usage. Further efforts are needed in the areas of behavioral science, health education, and public policy to tackle this urgent public health concern.